2022
DOI: 10.1016/j.wneu.2022.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Neurosurgery During the COVID-19 Pandemic: The Experience of Kazakhstan

Abstract: Background The practice of neurosurgery has been profoundly affected by the COVID-19 pandemic in Kazakhstan. Many elective surgeries were postponed or canceled which has resulted in difficulties in hospitalization. This study aims to describe the impact of COVID-19 on neurosurgical practice and to determine if there was a discrepancy in the effect between metropolises and regional cities in Kazakhstan. Methods We performed an electronic internet-based survey among Kazak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Dehora et al [ 28 ] found in an online survey with 176 responses from the Indian subcontinent that of all respondents, 46% were practicing restricted outpatient services, more so in public institutions, which also had a higher incidence of tele-outpatient services: 26% vs. 17% in private practice. Menlibayeva et al [ 29 ] reviewed the neurosurgical practice in Kazakhstan during a country-wide lockdown in July 2020 and found a decrease in consultations (65.34%) and surgeries (56.55%) by all neurosurgeons, regardless of city type. However, neurosurgeons attended online educational courses during the pandemic, mainly in major cities.…”
Section: Discussionmentioning
confidence: 99%
“…Dehora et al [ 28 ] found in an online survey with 176 responses from the Indian subcontinent that of all respondents, 46% were practicing restricted outpatient services, more so in public institutions, which also had a higher incidence of tele-outpatient services: 26% vs. 17% in private practice. Menlibayeva et al [ 29 ] reviewed the neurosurgical practice in Kazakhstan during a country-wide lockdown in July 2020 and found a decrease in consultations (65.34%) and surgeries (56.55%) by all neurosurgeons, regardless of city type. However, neurosurgeons attended online educational courses during the pandemic, mainly in major cities.…”
Section: Discussionmentioning
confidence: 99%
“…With the steady rise of new cases throughout 2020/21, the primary healthcare service in Kazakhstan was exponentially burdened. What would normally have been “essential” healthcare services, such as planned hospitalizations and healthcare for chronic illnesses, were halted as COVID-19 became the priority (Menlibayeva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%